Enteroparásitos asociados a diarrea aguda en niños menores de 12 años de edad - Rincón Wintila; Acurero Ellen; Serrano Elvia; Quintero Marisol; Beauchamp, Sharline (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2006)
Abstract: Diarrhea is a serious public health problem and intestinal parasites are one of causes of the same. In order to determine the prevalence of intestinal parasite species involved in acute diarrhea in children under 12 years of age, this study was carried out. The sample was 58 children of both sexes stratified in three age groups: less than 1 year old, of 1 to 4 years old and older than 5, from whom fecal samples were obtained to which analysis with the coproparasitological exam was applied with physiologic saline solution, lugol, blue from cushioned methylene, the coloration techniques, permanent modified Ziehl Neelsen and Acid Fast Tricromic testing. The obtained results indicated that 36,20% of the individuals presented intestinal parasites. The prevalence of identified enteroparasites was the following: Blastocystis hominis 17.24%, Complex Entamoeba histolytica /Entamoeba dispar 10,34%, Cryptosporidium parvum y Giardia lamblia both with 6,90%, Entamoeba coli 3.45%, Chilomastix mesnili, Endolimax nana and Pentatrichomonas hominis 1.72% each one. Statistical squared Chi analysis revealed significance between the variables parasitosis and male sex, age (5-12 years old) and monoparasitism (p<0.05). The results evidenced the persistence of intestinal parasites in children with acute diarrhea under 12 years of age. Resumen: La enfermedad diarreica representa un problema importante de salud pública, siendo las parasitosis intestinales una de sus causas. El objetivo de este estudio fue identificar especies de enteroparásitos asociados a diarrea aguda en niños menores de 12 años de edad. Se estudiaron 58 niños de ambos sexos estratificados en tres grupos de edad: menores de 1 año, de1a4 años y de5a 12 años. A cada niño se le tomó una muestra fecal a la cual se le practicó los métodos coproparasitológicos con solución salina fisiológica, coloraciones temporales con lugol y azul de metileno amortiguado y coloraciones permanentes de Ziehl Neelsen modificado y Ácido Rápido Tricrómica. El 36,20 % de los individuos presentaban enteroparásitos. Las especies parasitarias identificadas fueron las siguientes: Blastocystis hominis 17,24%, Complejo Entamoeba histolytica/E. dispar 10,34%, Cryptosporidium parvum 6,90%, Giardia lamblia 6,90%, Entamoeba coli 3,45%, Chilomastix mesnili, Endolimax nana y Pentatrichomonas hominis 1,72% cada uno. El Chi cuadrado reveló diferencias estadísticamente significativas entre las variables parasitosis y sexo masculino, edad (5-12 años) y monoparasitismo (p< 0.05). Estos resultados revelan la persistencia de estas infecciones en niños con diarrea aguda menores de 12 años.